Metathesis as Word Formation Process in Indonesian - Widiatmika, Putu Wahyu; Ni Komang, Ayu Wulandari; Ida Bagus Made, Ari Segara; Nissa Puspitaning, Adni (TALENTA, 2026)
Metathesis has long been regarded as a phonological process characterized by the rearrangement of sound segments within a word. However, recent linguistic trends in Indonesian suggest that metathesis has undergone a functional shift. Rather than occurring unintentionally in speech, Indonesian metathesis is deliberately produced and visually represented in written form, which creates new lexical items with stable orthographic patterns. This study aims to examine metathesis as a productive word-formation process in contemporary Indonesian. Employing a descriptive qualitative approach, this research utilizes a written corpus collected from X, selected through purposive sampling based on posts that contain metathesized forms in meaningful sentence contexts. Thirty metathesized lexical items were identified and classified into three types: full reversal, partial reversal, and syllabic reversal. The findings show that these forms follow recognizable phonotactic regularities rather than random alterations. Crucially, morphological testing reveals that metathesized words demonstrate both derivational and inflectional productivity. The ability of metathesized forms to serve as morphological bases confirms their status as autonomous lexical units within the mental lexicon of speakers. This study concludes that metathesis constitutes a legitimate and increasingly productive process of word formation in Indonesian.